The Influence of Quality of Working Life on Organizational Commitment of Nurses in General Hospital, Regional Health 3 - Phothiwan, Nanthiwa; Suntayakorn, Chanjar (NU Journal of Nursing and Health Sciences, 2019)
The purposes of this descriptive research were: First, to study the level of quality of working life of nurses in general hospital, Regional Health 3. Secondary, to study the level of organizational commitment of nurses in general hospital, Regional Health 3.and Third, to explore the influence of working life on commitment of nurses in general hospital, Regional Health 3. The sample consisted of 154 professional nurses who provided health care services to patients in the general hospital, Regional Health 3. Multistage sampling was used for selecting the study sample. The questionnaires consisted of three sections; 1) the demographic data 2) the quality of working life level of nurses in general hospital, Regional Health 3, and 3)the organizational commitment level of nurses in general hospital, Regional Health 3. The questionnaires were tested for validity and reliability. The Index of concurrence was 0.80 - 1.00. The Cronbach’s Alpha reliability coefficients of part 2 and 3 were 0.95 and 0.93 respectively. The data were analyzed using descriptive statistics (percentage, mean and standard deviation), Pearson’s product moment correlation and multiple regression analysis. Research findings were organized as following. First, the Quality of working life level of nurses in general hospital, Regional Health 3 at the medium level. Secondary, the organizational commitment level of nurses in general hospital, Regional Health 3 at the high level. and Third, Co-factors social relevance, development of human capacities, the total life space and growth and security could predict the organizational commitment(p < .01). These predictors accounted for 57.2 % (R2 = .572).